Systematic Literature Review : Evaluasi Dampak Stakeholder Setelah Revitalisasi Pasar Tradisional di Indonesia - Prasojo, Yaafi Rozaan; Muhith, Mochammad Rossy Dukhan; Veriyanto, Fanes Ardhito; Hermawan, Lukman; Hertati, Diana (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This study examines the impact of traditional market revitalization on stakeholders in Indonesia through a systematic literature review. The revitalization of traditional markets aims to increase competitiveness, improve physical conditions, and promote local economic growth. The method used was a systematic literature review in which 10 articles were selected from a Google Scholar search. The results show that revitalization has positive impacts, such as improved market cleanliness and convenience, but also negative impacts, such as reduced income for merchants and accessibility issues. Factors hindering the success of revitalization include inadequate communication, limited resources, resistance from traders and inappropriate market design. To optimize revitalization outcomes, a holistic assessment is needed that involves all stakeholders in planning, implementation and evaluation. Socialization, education and active community participation are also important to ensure the sustainability of the revitalization program. In summary, revitalizing traditional markets has great potential to improve market quality and support the local economy, but requires careful planning and the involvement of all stakeholders to ensure long-term success.